Statecraft strategies and housing financialization at the periphery: Post-socialist trajectories in Russia and Poland - MIrjam Büdenbender; Andrea Lagna (Finance and Society, 2019)
A new literature on housing and financialization has emerged in recent years, but scholars have yet to examine how political actors shape national trajectories of housing financialization. In this article, we address this shortcoming by examining the cases of Russia and Poland in the 1990-2018 period. We argue that in both contexts political elites implemented a radical market-oriented reshaping of housing finance. However, by pursuing distinct statecraft strategies and modes of integrating the domestic economy into global markets, Russian and Polish political elites created two divergent trajectories of housing financialization. Russian political elites pursued patrimonial statecraft strategies and a mode of global economic integration based on raw material exports. The Putin administration channeled revenues from raw material exports into the securitization-based housing finance system and used this infrastructure as an instrument of hegemonic power. In doing so, the Russian government shielded homeowners from exposure to financial risk. In contrast, Polish political elites pursued liberal statecraft strategies and a mode of global economic integration based on foreign capital inflows. Polish political parties therefore enabled foreign banks to dominate the housing finance system and sell foreign currency mortgages, which exposed homeowners to considerable financial risk. In light of these findings we call for further research into the political factors that shape the process of housing financialization, both in the post-socialist space and beyond.
Keywords: 300; Housing; financialization; financial innovation; statecraft; post-socialist capitalism